Political Price Cycles in Regulated Industries : Theory and Evidence - Paiva, Claudio (IMF Working Papers; Working Paper, 2006)
This paper develops a model of political regulation in which politicians set the regulated price in order to maximize electoral support by signaling to voters a pro-consumer behavior. Political incentives and welfare constraints interact in the model, yielding an equilibrium in which the real price in a regulated industry may fall in periods immediately preceding an election. The paper also provides empirical support for the theoretical model. Using quarterly data from 32 industrial and developing countries over 1978-2004, we find strong statistical and econometric evidence pointing toward the existence of electoral price cycles in gasoline markets.